Early implementation of screening for substance use in rural primary care: A rapid analytic qualitative study. Issue 4 (October 2021) - Moore, Sarah K.; Saunders, Elizabeth C.; Hichborn, Emily; McLeman, Bethany; Meier, Andrea; Young, Robyn; Nesin, Noah; Farkas, Sarah; Hamilton, Leah; Marsch, Lisa A.; Gardner, Trip; McNeely, Jennifer
Background: Few primary care patients are screened for substance use. As part of a phased feasibility study examining the implementation of electronic health record-integrated screening with the Tobacco, Alcohol, and Prescription Medication Screening (TAPS) Tool and clinical decision support (CDS) in rural primary care clinics, focus groups were conducted to identify early indicators of success and challenges to screening implementation. Method: Focus groups ( n  = 6) were conducted with medical assistants (MAs: n  = 3: 19 participants) and primary care providers (PCPs: n  = 3: 13 participants) approximately one month following screening implementation in three Federally Qualified Health Centers in Maine. Rapid analysis and matrix analysis using Proctor's Taxonomy of Implementation Outcomes were used to explore implementation outcomes. Results: There was consensus that screening is being used, but use of the CDS was lower, in part due to limited positive screens. Fidelity was high among MAs, though discomfort with the CDS surfaced among PCPs, impacting adoption and fidelity. The TAPS Tool's content, credibility and ease of workflow integration were favorably assessed. Challenges include screening solely at annual visits and self-administered screening for certain patients. Conclusions: Results reveal indicators of implementation success and strategies to address challenges to screening for substance use in primary care.